Analisis Tentang Kewajiban Nafkah Keluarga Dalam Pemberlakuan Harta Bersama - Jumni Nelli (AL-ISTINBATH : Jurnal Hukum Islam, 2017)
In Islam, a nafkah is the responsibility of a husband. As in Indonesia family lawappliesthat nafkahis the responsibility of a husband and also it imposes joint property. The obligation of a husband to feed raises an issue regarding the implementation of obligations of a husband that can lead to a legal loophole that could undermine the principle of legal certainty and justice community. It is important to be discussed about nafkah and the concept of joint property in Islamic law and KHI, as well as the obligations to provide nafkah for her husband. Based on this research, understandably ifjoint property was appliedthen it becomes the collective responsibility of husband and wife. It also brings the consequence that all the household duties can beduties in together. Thus Islam adheres to the principle of balance and fairness in the relationship of husband and wife.